Intelligent biobased hydrogels for diabetic wound healing: A review - Wang, Hanzhang; Zhang, Li-Ming (Chemical engineering journal (Lausanne, Switzerland : 1996), 2024)
•The intelligent hydrogel in the diabetic wound microenvironment was highlighted.•The application value of biobased materials in intelligent hydrogel was described.•The chemical structure and synthetic method of intelligent hydrogel were elucidated.•The therapeutic strategies and effects of intelligent hydrogel were summarized. Slow wound healing induces great pain in diabetic patients. However, developing new approaches to promote diabetic wound healing is still one of the toughest challenges. This review described an overview of intelligent hydrogels based on biomaterials in diabetic wound dressings, focusing on their chemical design and practice. We elucidated the synthesis principles of intelligent hydrogels and described the application effectiveness of hydrogels in repairing diabetic wounds based on the changes in the diabetic wound microenvironment. We summarized the preparation and mechanism of intelligent hydrogels, including stimulus–response, injectable, self-healing, and electrical conductivity. The roles of intelligent biobased hydrogels in treating diabetic wounds, including antibacterial, hemostatic, angiogenic, anti-inflammatory, and antioxidant properties, and the synergistic effects were discussed. We also highlight the advantages and limitations of biomaterials with different active ingredients in hydrogels. Furthermore, the main challenges and future directions in developing diabetic wound dressings are proposed.